Constructing a model for assessing knowledge transfer - Md Dahalin, Zulkhairi; Suebsom, Korawan (2008)
Knowledge transfer is important in the educational system. Most universities emphasized on the effectiveness of knowledge transfer from the instructor to learners since the effectiveness of knowledge transfer can improve the teaching methods.This paper describes the model that can explain the assessment of knowledge transfer from the instructor to learners.The model is based on the knowledge and experience of the authors in the educational environment plus the extensive literature search on the subject. The authors used experimental research and collected data from thirty respondents to represent the model for assessing knowledge transfer.The authors hope that this model can explain the effectiveness of knowledge transfer through improvement to the teaching methods for instructors and also improve the learners’ learning in the higher education system.